PENGARUH TRANSPARANSI DAN AKUNTABILITAS TERHADAP PENGELOLAAN ANGGARAN PENDAPATAN DAN BELANJA DESA (Studi pada Seluruh Desa di Kecamatan Kadipaten) - Melia Wida Rahmayani; Engkun Kurnadi (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2022)
ABSTRACT The management of the village income and expenditure budget carried out by several villages in the Duchy District has not been in accordance with the legislation and the implementation of village deliberations has not been maximized to discuss and explain the management of the APBDes. This study aims to determine the effect of transparency and accountability on the management of the Village Revenue and Expenditure Budget. This research is a survey research using descriptive verification method, the population of this research is all village heads and village officials in the Kadipaten District using a total sampling of 63 people. Data collection was done by survey method using a questionnaire. Data analysis used descriptive analysis and verification analysis including classical assumption test, multiple linear regression analysis, coefficient of determination analysis and model feasibility test. Test the hypothesis using the t test. The results showed that transparency had a significant effect on the management of the APBDes in the Kadipaten District, Majalengka Regency, meaning that the more transparent the management of the APBDes, the management of the APBDes would be better. Accountability has a significant effect on the management of the APBDes in the Kadipaten District, Majalengka Regency, meaning that the more accountable the APBDes management is, the better the APBDes management will be.